BUSINESS STRATEGY FORMULATION AT NAVIRE, AN OUTDOOR JACKET BUSINESS, BASED ON STRATEGIC MANAGEMENT PROCESS - Riandiza, Bima; Wandebori, Harimukti (Journal of Business and Management, 2018)
Abstract. Navire hosts massive potential during its year due to the trend and unique product offering. Howe ver, the company ended its run. There is clear intention from executives of Navire to continue their business. The executives claimed they are struggle to formulate cohesive business strategy. In strategic management, business strategy formulation is very important. The goal of this research is to formulate business strategy for Navire. Strategic management process is used as a theoretical framework. Theories that were used in based on the theoretical framework, with the addition of Costumer Behavior and marketing strategy; Market STP, and Marketing Mix. The inclusion of Customer Behavior Model is to reassess the market again as data provided by executives of Navire is already irrelevant. The findings of this research are, the general environment are supportive. Demographically, Navire market, based on the questionnaire result divided into 5. The industry is expected to grow and holds an attractive proposition. In terms of rivalry, the industry is deemed to be at medium level. Competitor environment analysis result concludes each competitor have their own unique capabilities. Internal environment of the company also analyzed with resource analysis and value chain analysis. This information was then assessed and strategies are made. The business strategy appropriate for Navire is Integrated Cost Leadership/Product Differentiation for business-level strategy.Keywords: Customer Behavior, IBE Business, Business Strategy, Strategic Management Process